Cause Related Marketing: An Incitement Strategy - Srinivasulu, Yarlagadda (Indian Journal of Marketing, 2006)
The changes in the environment have necessitated the need to review the present business philosophy. Companies have incorporated social goals as a part of their mission statement. Corporate involvement in social well-being began as voluntary responses to social issues and problems, then evolved into a phase of mandated corporate involvement and is now evolving in to a phase in which social responsibility is viewed as an investment by corporations. Corporations are beginning to realise that, for their survival and competitive advantage, they must evolve from doing good to doing better. Therefore, social responsibility is treated as an investment that improves the long-term performance of the organisation.1 Socially responsible practices have resulted in a favourable image and ultimately in increased sales. Organisations identified the need to bring a trade off between economical motives and social values.